Dirasah Muqaranah ‘an Hukm al-Zawaj Bayna Rudha’a Alban Bunuk al-Laban Fi Manzhur Fuqaha al-Aqdamin wa al-Mu’ashirin - Harahap, Khoirul Amru; Umar, Muhammad Toha (Jurnal Syariah dan Hukum Komparatif, 2024)
The issue of Breast Milk Bank is a contemporary fiqh issue, and its ruling is not found in classical fiqh. However, classical Moslem scholars have studied the issue of radha in an unusual way known as al-major (breast milk put into the baby's mouth), al-south (breast milk put through the nose), and or putting breast milk into the baby's mouth using bottles and cups. Therefore, the fuqaha differed on the prohibition of marriage because of radha' unusually or indirectly such as radha' from a breast milk bank. After conducting a comparative analysis, the author concludes that the majority of classical scholars from the Hanafi, Maliki, Shafi'i and Hambali madhhabs, and most contemporary fiqh scholars, think that indirect radha', such as radha' from a breast milk bank, makes marriage prohibited. They reason that indirect radha' has the same effect as direct radha' regarding the growth of the baby's flesh and bones. Meanwhile, the Zhahiri school of classical jurisprudence and some contemporary jurisprudence scholars such as Yusuf al-Qardhawi think that indirect radha' such as radha' from a breast milk bank is not called radha'. According to them, radha' is only if the baby suckles directly on the mother's nipple. Hence, they think that radha' from a breast milk bank does not lead to the prohibition of marriage.